A Study on Orthographic Errors in Chinese Character Acquisition and Instructional Strategies for Students of Chinese Descent in Spain - Jinxian, Huang (Sinología hispánica. China Studies Review, 2026)
This study investigates the acquisition of Chinese characters by students of Chinese origin in Spain. Employing a research methodology that combines qualitative and quantitative approaches, a systematic analysis was conducted on the orthographic errors found in a corpus of 83 essays. The aim is to classify the characteristics of these errors, investigate their underlying causes, and, based on this, propose corresponding teaching strategies. The findings reveal that, at a macro level, incorrect characters (characters with flawed form) constitute the main type of error. A more detailed micro-analysis shows that: regarding incorrect characters, the errors of intermediate-level learners are primarily concentrated at the stroke level, whereas those of advanced learners mainly manifest at the structural component level. In the dimension of confused characters (using the wrong character), intermediate learners tend to confuse characters with similar pronunciations, while advanced learners primarily confuse characters with similar forms. Based on these characteristics and their causes, this study proposes specific teaching strategies and recommendations for Chinese character instruction targeted at students of Chinese origin in Spain.